Penerapan Menu Makan Sehat Dengan Gizi Seimbang Melalui Bekal Anak di RAM NU 152 Wagir Lor Ngebel Ponorogo - Nita Khoirum; Soni Amrullah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This community service program aims to educate and improve parents' understanding of the importance of providing healthy and balanced meals in their children's lunchboxes. This program uses the ABCD method. The findings show that the provision of nutritionally healthy and balanced meals in children's lunchboxes still does not fully meet their nutritional needs. These meals do not follow balanced nutritional guidelines properly. Most lunchboxes are dominated by double protein, and very few include additional vegetables or fruits. The implementation of the Nutrition Day Program initiated by the school was developed through a parenting seminar with the theme of applying a healthy and nutritionally balanced diet through children's lunchboxes, which had a positive and significant impact on forming healthy eating habits. In addition, it was also useful for educating and increasing parents' knowledge and awareness of the importance of applying a balanced diet, especially through children's lunchboxes.